RESPON KONSUMEN TERHADAP PEMBERITAAN DITEMUKANNYA FORMALIN PADA PRODUK PANGAN OLAHAN (CONSUMERS RESPONSE TOWARDS NEWS OF THE FORMALIN USAGE ON PROCESSED FOOD PRODUCT) - -, WIDODO; YUSI RUDIMAH, SITI (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol. 8, No. 2 Juli 2008, 2012)
The negative news about small or home industries food production that was published by mass media has a large impact on it’s marketing. This research was conducted to explain the attitude and consumers behaviour change toward food that was issued of formalin usage to preserving. This descriptive research was conducted with survey to 42 households in urban, 50 households in sub urban, and 26 householeds in rural territory. The results showed that negative news of formalin usage to food preserving decreased the consumer’s believe towards the food safety, the tendency to consume, rose the consumer buying selectivity and decreased the consumer buying intensity. The consumer’s believe towards the food safety, the tendency to consume, the consumer buying intensity will increased after the publishing of promotif news such as public figure consuming that food, but the buying selectivity still arose. The positive news of no formalin usage on food that was published increased again the consumer’s believe towards the food safety, the tendency to consume, the consumer buying selectivity and the consumer buying intencity but not recovered
Keywords: Mass Media, Formalin, Processed Food, Attitude, Consumer Behaviour